Lowered Serum Testosterone Concentration Is Associated With Enhanced Inflammation and Worsened Lipid Profile in Men - Grandys, Marcin; Majerczak, Joanna; Zapart-Bukowska, Justyna; Duda, Krzysztof; Kulpa, Jan K.; Zoladz, Jerzy A. (Frontiers in Endocrinology, 2021)
The relationship between testosterone and inflammatory cytokines has been reported since decades, although the exact mechanisms of their interactions are still not clear. At the same time, little is known about the relation between androgens and acute phase proteins. Therefore, in this investigation we aimed to study the relationship between androgen status and inflammatory acute phase reactants in a group of men using multi-linear regression analysis. Venous blood samples were taken from 149 men ranging in age from 18 to 77 years and gonadal androgens (testosterone – T, free testosterone – fT), acute phase reactants (c-reactive protein – CRP, ferritin – FER, alpha-1-acid glycoprotein – AAG, interleukin-6 – IL-6), cortisol – C and lipid profile concentrations were determined. It was demonstrated that markers of androgen status (T, fT) were negatively correlated with all acute phase proteins (CRP, FER and AAG; P<0.02) and blood lipid profile (TC, LDL and TG; P<0.03). Multivariate analysis showed that T, fT and fT/C ratio were inversely correlated with CRP, AAG and FER concentrations, independently from age and blood lipids. However, when adjustment for BMI was made, androgen profile was negatively correlated with AAG concentrations only. In addition, it was demonstrated that androgen profile was positively correlated with physical activity level (P<0.01). We have concluded that lowered serum T concentration may promote inflammatory process independently from adipose tissue and age through reduced inhibition of inflammatory cytokines synthesis which leads to enhanced acute phase protein production. Therefore, low serum T concentration appears to be an independent risk factor in development of atherosclerosis and cardiovascular diseases. Moreover, the positive correlation between testosterone and physical activity level suggests that exercise training attenuates age-related decrease in gonadal androgens and in this way may reduce the enhancement of systemic low grade inflammation in ageing men.